2014
DOI: 10.1161/atvbaha.113.302696
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bone Morphogenic Protein 4 Restores Endothelial Function in db/db Diabetic Mice

Abstract: Objective— Bone morphogenic protein 4 (BMP4) is involved in the development of endothelial dysfunction in hypertension. This study investigated whether the inhibition of BMP4 signaling improves endothelial function in db/db diabetic mice. Approach and Results— Male db/db mice were treated with noggin via osmotic pump infusion (1 µg/[h·kg –1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…54 Different strategies inhibiting BMP4 in diabetic db/db mice reduce reactive oxygen species production and rescued endothelium-dependent relaxations. 55 Similar findings are observed after inhibition of activin receptor-like kinase 3, a pathway downstream of BMP4 receptor. Regulation of the BMP4 pathway might therefore represent an interesting therapeutic strategy to fight endothelial dysfunction in diabetes mellitus.…”
Section: Endothelium In Diseases Diabetes Mellitussupporting
confidence: 58%
“…54 Different strategies inhibiting BMP4 in diabetic db/db mice reduce reactive oxygen species production and rescued endothelium-dependent relaxations. 55 Similar findings are observed after inhibition of activin receptor-like kinase 3, a pathway downstream of BMP4 receptor. Regulation of the BMP4 pathway might therefore represent an interesting therapeutic strategy to fight endothelial dysfunction in diabetes mellitus.…”
Section: Endothelium In Diseases Diabetes Mellitussupporting
confidence: 58%
“…12 Here we also found increase of plasma PDGF-AA in diabetic human and db/db mice. Importantly, we found that antagonizing PDGF-AA improves endothelium-dependent vasodilation in db/db mice, 12 indicating PDGF-AA as a new risk factor to cause vascular dysfunction. We also showed that inhibition of Smad1/5 and Smad4 abolished BMP4-induced PDGF-AA.…”
Section: Discussionsupporting
confidence: 70%
“…BMP4 is also involved in endothelial dysfunction of db/db mice. 12 Here we tested whether PDGF-AA is a risk factor leading to endothelial dysfunction in db/db mice as well. We found higher plasma level of PDGF-AA in diabetic patients (fasting glucose >7.0 mmol/L) compared with nondiabetic subjects ( Figure 5A), whereas PDGF-BB levels were similar ( Figure tolerance and insulin tolerance were similar between Ad-GFP (as control) and Ad-Pdgfa-shRNA-treated mice ( Figure VG and VH in the online-only Data Supplement).…”
Section: Upregulation and Function Of Pdgf-aa In Diabetic Vascular Dymentioning
confidence: 99%
See 1 more Smart Citation
“…Changes of isometric tension of aortas were recorded in a wire myograph (Danish Myo Technology), and FMD was determined in a pressure myograph (60). For FMD study, the vessel diameter was continuously monitored on a lightinverted microscope (Zeiss Axiovert 40 Microscope, model 110P) through a video camera operated on the Myo-View system (Danish Myo Technology).…”
Section: Functional Studymentioning
confidence: 99%